2016
DOI: 10.18632/oncotarget.7089
|View full text |Cite
|
Sign up to set email alerts
|

Setdb1, a novel interactor of ΔNp63, is involved in breast tumorigenesis

Abstract: ΔNp63 has been recently involved in self-renewal potential of breast cancer stem cells. Although the p63 transcriptional profile has been extensively characterized, our knowledge of the p63-binding partners potentially involved in the regulation of breast tumour progression is limited. Here, we performed the yeast two hybrid approach to identify p63α interactors involved in breast tumorigenesis and we found that SETDB1, a histone lysine methyl transferases, interacts with ΔNp63α and that this interaction contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Downregulation of SETDB1 in the BT549 and MDA-MB-231 cells reduced cell proliferation, whereas SETDB1 upregulation in MCF7 and T47D cells enhanced proliferation. Recently, Regina et al (29) reported that SETDB1 is overexpressed in breast cancer cell lines and enhanced tumor cell growth, which is consistent with the findings of the current study. Additionally, depletion of SETDB1 suppressed cell migration and invasion in vitro and reduced lung metastasis in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…Downregulation of SETDB1 in the BT549 and MDA-MB-231 cells reduced cell proliferation, whereas SETDB1 upregulation in MCF7 and T47D cells enhanced proliferation. Recently, Regina et al (29) reported that SETDB1 is overexpressed in breast cancer cell lines and enhanced tumor cell growth, which is consistent with the findings of the current study. Additionally, depletion of SETDB1 suppressed cell migration and invasion in vitro and reduced lung metastasis in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we identified the expression of SETDB1 and H3K9me1 were significantly upregulated in CCA tissues cells, as compared to that in normal tissues or HIBEC cell. These results suggested that SETDB1 were indeed up-regulated in CRC as well as in other solid tumors [22,24]. On the other hand, survivin is an oncogene that regulates the apoptosis, proliferation, and invasion of many cancers [25][26][27].…”
Section: Discussionmentioning
confidence: 86%
“…SETDB1 protein belongs to the SET-domain (Su(var)3-9, E(z), Thrithorax) protein methyltransferase family [21], which is mainly involved in tri-methylation of H3K9 and usually cause gene silencing or transcription inhibition. In recent years, mounting evidence has linked the aberrant high expression of SETDB1 to the human carcinogenesis, including melanoma, lung cancer, breast cancer, ovarian cancer [22][23][24]. Further investigations are ongoing to explore the underlying mechanism of epigenetic modifications by SETDB1.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been proposed that SETDB1 indirectly up-regulates STAT3 expression and induces TWIST and C-MYC to potentiate this process [125]. Alternatively, SETDB1 stabilizes ΔNp63α through protein interaction while ΔNp63α might recruit SETDB1 to repress multiple EMT-related genes [126]. Additionally, amplification of SETDB1 was observed in melanoma, lung and liver cancers [127129].…”
Section: Permissive Histone Modifications In Emtmentioning
confidence: 99%